(untitled) (International Current Pharmaceutical Journal, 2015)
The aim of the present work is to synthesize and evaluate the anti-inflammatory and analgesic activity of 2-(5-substituted-1,3,4-oxadiazole-2-yl)-1,3-benzathiazole derivatives. In the present investigation, a series of 2-(5-substituted-1,3,4-oxadiazole-2-yl)-1,3-benzathiazole derivatives (3a1-3a9) were synthesized by condensing benzothiazolyl carboxyhydrazide and appropriate aryl acids in the presence of phosphorous oxychloride. Structures of synthesized compounds were established on the basis of IR, 1H NMR, and Mass spectroscopy. All the synthesized compounds were screened for their in-vivo anti-inflammatory and analgesic activities at the dose of 50 mg/kg and 10 mg/kg po. The biological result shows that some compounds were good in their anti-inflammatory and analgesic actions. Kumar et al., International Current Pharmaceutical Journal, November 2015, 4(12): 457-461